EFL Learners’ Intercultural Competence Development Through International News - Gómez-Rodríguez, Luis Fernando (GIST – Education and Learning Research Journal, 2018)
This case study analyzed how a group of English learners built critical intercultural awareness through the discussion of cultural events as reported in news media such as The New York Times, the U.S. News, and The Telegraph. Learners’ critical reflections on controversial social conflicts related to injustice, gender inequality, and stereotypes in different cultures constituted the core data collected through field notes, logs, and one questionnaire. Findings revealed that English learners not only gained new knowledge about beliefs, values, and behaviors that cause conflict in other cultural communities, but compared them critically to their own culture. This research concluded that integrating news in EFL education can be a salient instructional material to help EFL speakers become more critical intercultural individuals through topics belonging to deep culture.